Biosignature of self-injury behaviors in adolescence: Role of β-endorphin in an acute inpatient unit - Wang, Ping; Li, Chao; del Sol-Calderón, Pablo; Mallol, Leticia; Hernández-Álvarez, Elena; Donoso-Navarro, Encarnación; Gil-Ligero, María; Rosado-Garcia, Silvia; Sánchez-Lòpez, Antonio José; Martín-Moratinos, Marina; Bella-Fernández, Marcos; Blasco-Fontecilla, Hilario (Frontiers in Psychiatry, 2022)
Self-injurious behavior (SIB) is a common reason for adolescent psychiatric emergency hospitalizations. Increased serum β-endorphin(BE) levels have been reported in adult patients addicted to SIB, but information is lacking in adolescents. We analyzed the serum BE level and psychopathologic profile of 39 adolescent inpatients admitted to the acute unit at Puerta de Hierro University Hospital (Majadahonda, Spain) due to SIB (either non-suicidal self-injury, NSSI; or suicide attempts, SA). Adolescent inpatients had very high serum BE levels. Furthermore, those adolescents addicted to SIB had higher BE serum levels, although non-statistically significant (196.17± 74.19 vs. 147.73 ± 63.48, F=1.82 p= 0.186). However, patients with depression as their primary diagnosis had a lower BE level than those with other diseases as their primary diagnosis (F=8.13, p=0.007). Furthermore, adolescent inpatients who increased time spent on SIB in order to feel better had a lower BE level than those who did not meet this suicide addiction criteria (F=4.14,p=0.05). The majority of patients began their SIB with NSSI which later progressed to SA. The time interval between NSSI and SA reduced with an older age at first-time NSSI (marginally non-significant, p=0.06). The relationship between serum BE levels and SIB in adolescents require further investigation.